ASSESSMENT OF FACTORS INFLUENCING SETTING OF REALISTIC TARGETS ON SERVICE DELIVERY OF NATIONAL GOVERNMENT ADMINISTRATIVE OFFICERS, KAKAMEGA COUNTY KEN YA - Biwott, Josphat Kibet; Kembu, Appolonius Shitiabai (IJRDO - Journal of Business Management, 2016)
he ever increasing demand for quality service delivery in the public sector triggered the development of Rapid Result Initiative as a result-focused learning process aimed at jumpstarting major change efforts through a series of small-scale, results producing and momentum-building initiatives. The main purpose of the study was to assess the influence of Setting Realistic Targets on service delivery of National Government Administrative Officers at Kakamega County. The Sample consisted of 105 employees from the total population of 347 employees, Stratified Random sampling was used. Data was collected through questionnaires. In the analysis descriptive statistics, correlation analysis and simple regression analysis was performed to establish whether there is statistically significant relationship between setting realistic targets and service delivery. A conclusion was drawn and sought that there is strong relationship between setting of realistic targets and service delivery.